AFFECT IN EXPRESSIVE SPEECH ACTS BY THE JUDGES OF THE VOICE UK VERSUS THE VOICE VIETNAM - Ngoan, Nguyen Quang; Loc, Le Huu (VNU Journal of Foreign Studies, 2020)
Appraisal Theory by Martin and White (2005) has increasingly claimed its potential in discourse analysis studies, highlighting the speakers’ and writers’ evaluations of people, entities, and events. This paper adopts Martin and White’s Appraisal framework for the purpose of determining the Affect in the expressives made by the judges of the two reality shows, The Voice UK versus The Voice Vietnam. Specifically, the research addresses itself to discovering which Affect resources are used in the expressive acts by the judges and indicating the resemblances and discrepancies in employing those resources in the expressives by the two groups of judges. The results reveal that all of the sub-types of Affect were found in the two data sets. Besides, the Affect resources in the two languages share a variety of similarities in terms of their frequency, realization strategies, and polarities. The study can be the reference for learners of English and Vietnamese in passing their remarks in daily communication.